ANALISIS PENERAPAN PSAP NOMOR 2 TENTANG LAPORAN REALISASI ANGGARAN DENGAN TINGKAT KESEJAHTERAAN MASYARAKAT PADA PEMERINTAHAN KABUPATEN KETAPANG - Liandini B51112147, Syiera Fitri (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The purpose of this study to determine the suitability of the Pernyataan Standar Akuntansi Pemerintahan (PSAP) Number 2 on the Budget Realization Report on the level of Public Welfare in Ketapang. This research uses descriptive method with qualitative approach. The Data used by the researchers is data obtained directly by the Chief Financial Officer of Ketapang and data that has been in though and are available at the Badan Pusat Statistik Ketapang. Data obtained through questionnaires, archival research and literature study. The results of comparative evaluation of the application of the PSAP Number 2 with evidence of its implementation shows that the Budget Realization Report Ketapang has been applied in accordance with the PSAP Number 2. Human Development Index (HDI) of Ketapang category that has a low HDI group, so that the public welfare of Ketapang is still relatively low. Keywords : Governmental Accounting Standards Board, Budget Realization Report, Publik Welfare, Human Development Index.